Pendidikan Formal Anak Pada Keluarga Miskin di Kelurahan Sialangmunggu Kecamatan Tuah Madani Kota Pekanbaru - Muhammad Naufal Raihan Ali; Hesti Asriwandari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study aims to analyze the influence of the socio-economic conditions of poor families on the formal education of children in Sialangmunggu Subdistrict, Tuah Madani District, Pekanbaru City. The background of this research is based on the fact that education is an essential need for human survival, and the quality of life of an individual is greatly determined by the level of education they attain. However, access to quality education remains a challenge for families with low economic backgrounds. This research uses a qualitative approach with the theoretical framework of symbolic violence as explained by Pierre Bourdieu, which describes how social structures can create and maintain inequality in access to education. Data was obtained through in-depth interviews with research subjects who are parents from poor families in the study location. The results of the study indicate that the family's economic limitations significantly affect the children's education, as seen from the low level of educational participation, difficulties in meeting educational needs, and the psychological impact on children. Parents from poor families often face difficult choices between meeting daily needs and ensuring their children remain in school. The conclusion of this study indicates that efforts to improve access and quality of education for poor families are essential to break the cycle of poverty and enhance social mobility.